Advances in manufacturing multi-layer materials for thermal camouflage applications - Nguyen, Ngoc Son; Nguyễn Mạnh Thắng; Vũ Đức Hiếu; Nguyen Anh, Dr.Tuan (Journal of Military Science and Technology, 2024)
Thermal imaging reconnaissance technology has been widely and effectively exploited in the military sector to serve reconnaissance, search and track objects and other purposes, because the heat signature of any target is very difficult to conceal, and easily be detected by thermal imaging reconnaissance devices. Thermal imaging camouflage covers are researched and developed to limit detection by thermal imaging devices by minimizing the heat signature of the target. Multi-layered Textile Structures (MTS) coverings are proposed basing on overlapping layers of different materials, combining and optimizing the properties of individual materials to create one with thermal camouflage properties. This article studied and summarized national and international research on thermal imaging camouflage coverings with multi-layer structures, as a basis for orienting research, developing a design method, optimizing and manufacturing a covering with a multi-layer structure that effectively thermal camouflages by domestic resources.